The Nexus of Ownership Structure, Profitability, Financing and Firm Value: Testing the Moderating Role of Firm Size - Eva, Lidwina; Hartono, Hartono; Santoso, Hadi (Journal of Management and Administration Provision, 2025)
This study aims to analyze the influence of managerial ownership, institutional ownership, profitability, and leverage on firm value, with firm size as a moderator. High firm value will send a positive signal to investors. This quantitative study uses 165 observational data obtained from the financial statements of non-cyclical consumer sector companies (2019-2023). This research tests eight hypotheses using panel data regression involving firm size as a moderating variable (Moderated Regression Analysis–MRA). The results show that institutional ownership and leverage (DER) have no effect on firm value. Meanwhile, managerial ownership shows a positive effect on firm value, and profitability (ROE) shows a negative effect on firm value. Furthermore, in testing the moderation model, the firm size variable weakens the effect of institutional ownership on firm value. This interaction effect is not apparent in testing managerial ownership (MAN), profitability (ROE), and leverage (DER) on firm value (PBV). Other findings indicate that firm size in the study does not act as a pure moderator, but rather as a quasi-moderator.